2016
DOI: 10.1186/s12879-016-1937-9
|View full text |Cite
|
Sign up to set email alerts
|

Validation of genotype cluster investigations for Mycobacterium tuberculosis: application results for 44 clusters from four heterogeneous United States jurisdictions

Abstract: BackgroundTracking the dissemination of specific Mycobacterium tuberculosis (Mtb) strains using genotyped Mtb isolates from tuberculosis patients is a routine public health practice in the United States. The present study proposes a standardized cluster investigation method to identify epidemiologic-linked patients in Mtb genotype clusters. The study also attempts to determine the proportion of epidemiologic-linked patients the proposed method would identify beyond the outcome of the conventional contact inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…We categorized M.tb strains into five groups, and the dominant isolates were category IV, accounting for 77.46% of all isolates. We observed that the RD105 deletion (Beijing family) contributed to the predominant infection, which was consistent with findings by Larry D. Teeter (23) and Carlo Garzelli (24). In addition, we found a significant association between non-dominant strains and pulmonary cavitation, which was consistent with the report by Lazzarini (25).…”
Section: Discussionsupporting
confidence: 92%
“…We categorized M.tb strains into five groups, and the dominant isolates were category IV, accounting for 77.46% of all isolates. We observed that the RD105 deletion (Beijing family) contributed to the predominant infection, which was consistent with findings by Larry D. Teeter (23) and Carlo Garzelli (24). In addition, we found a significant association between non-dominant strains and pulmonary cavitation, which was consistent with the report by Lazzarini (25).…”
Section: Discussionsupporting
confidence: 92%
“…A key goal is to detect and interrupt transmission early enough to prevent incident genotypes from becoming epidemiologically entrenched in the population. In the United States, molecular surveillance [ 99 ] to detect and characterize clusters that may represent recent transmission has facilitated progress toward this goal [ 100 ]. In tandem, rapid uptake of technologies for WGS and phylogenetic analysis of select clusters that likely represent recent transmission has shown considerable promise in more precisely identifying outbreaks and outbreak-related cases.…”
Section: Heterogeneity Of Transmission: Where Is Tuberculosis Transmimentioning
confidence: 99%
“…From 44 PCRType clusters randomly selected in our previous study [17], fifty-nine patients with incomplete MIRU24 results (including 13 patients for the entire clusters 3 and 31 from MD and GA respectively) were excluded from the analysis. In total, 42 clusters consisting of 342 patients having complete MIRU24 results were included in the current study (Appendix A).…”
Section: Resultsmentioning
confidence: 99%
“…For patients in selected PCRType-based study clusters with Mtb isolates characterized prior to the 2009 transition to MIRU24, retrospective MIRU24 typing was performed. The study sample selection has been described in detail elsewhere [17]. Briefly, PCRType clusters were defined as two or more TB patients with the same PCRType in a given public health jurisdiction during the study period.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation